FAKTOR – FAKTOR PENGAMBILAN KEPUTUSAN ORANG TUA DALAM MEMILIH SEKOLAH MENENGAH ATAS WILAYAH JAKARTA TIMUR - elvira elvira (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
School Services in order to be successful in the competition try to create and retain customers by managing marketing strategies, namely by word of mouth, location, social influence on parents' decision making in choosing high school. Schools By making advertisements in the form of brochures and banners, then distributing them in crowded places or the city center. Can influence parents' decision making in choosing a high school. survey research method, in which information is collected from respondents using a questionnaire. The type of data needed in this study is primary data and secondary data with a sample of 120, the hypothesis test used is the T test. The results show that words of mouth affect decision making, influence decision making, social influences affect parents' decision making in choosing high school. The limitations of this study are that it only uses word of mouth, location, social influence and decision-making variables